IODP Expedition 382, Hole U1536E - Well Logging Data - Weber, Michael; Raymo, Maureen Mo; Williams, Trevor; Armbrecht, Linda; Bailey, Ian; Brachfeld, Stefanie; Du, Zhiheng; Fauth, Gerson; Garcia, Marga; Gluder, Anna; Guitard, Michelle; Gutjahr, Marcus; et al. (Zenodo, 2021)
Logging data are measurements of physical properties of the formation surrounding a borehole, acquired in situ after completion of coring (wireline logging) or during drilling (Logging-While-Drilling, LWD). The range of data (resistivity, gamma radiation, velocity, density, borehole images,…) in any hole depends on the scientific objectives and operational constraints. : IODP Expedition 382: Iceberg Alley snd Subantarctic Ice and Ocean Dynamics